DYNAMIC TRUST MANAGEMENT. - Blaze, Matt; Kannan, Sampath; Lee, Insup; Sokoisky, Oleg; Smith, Jonathan M.; Keromytis, Angelos D.; Lee, Wenke (Computer (00189162), 2009)
The article examines dynamic trust management within the context of the Global Information Grid (GIG), an ongoing collaboration between the U.S. Department of Defense and Intelligence Community. Topics include problems with the GIG architecture, challenges to service-oriented architectures, dynamic trust management, trust management architecture, trust policy language, cooperative policy evaluation and feedback, system prototyping, and synergies. The authors conclude with a discussion of the current and future paths of their research in trust management.